Senior Female EFL Teachers' Voices: Beliefs on ICT Implementation In EFL Classrooms - Nur Lailiyah Jamil; Sari Karmina; Siti Muniroh; Latisha Asmaak Shafie (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2023)
The pandemic caused by COVID-19 has led to increased ICT usage in educational institutions. Still, senior teachers who have a significant impact on their advancement of professionalism with many years of teaching experience face several challenges in utilizing ICT in teaching and learning. Several studies found that compared to male teachers, female teachers are less proficient in using ICT devices due to several factors. Thus, this study aims to discover senior female EFL teachers' beliefs in terms of their perceptions and awareness of using ICT during their teaching and learning processes. The study included 34 senior female EFL teachers from East Java, Indonesia. A sequential explanatory mixed-methods design was used in this study. The questionnaires and one-on-one interviews showed that the use of ICT in the classroom is reported to be well appreciated by senior female EFL teachers, who also received guidance and support from their colleagues and collaborated on ICT professional development. However, they need assistance with theoretical and practical ICT abilities, solutions to internet constraints, and school-based technological infrastructures. This study recommends the government and higher education institutions implement targeted programs for senior teachers.